The evolution of the Case-Law of the European Court of Human Rights in the foster care and the right to maintain the family tight with the biological parents: : The Norwegian cases and two Spanish cases - Elósegui, María (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
This article analyzes the general principles on foster care estblished in the jurisprudence of the ECHR from its judgment Strand Lobben v. Norway, as well as the Resolution of the parliamentary Assembly of the Council of Europe in favor of the ties with the family of origin when the intervention of the guardianship of the administration in the care of minors is necessary. Below is a critical analysis of two cases ruled against Spain by the ECHR, cases Haddad and Omorefe, as well as the similarities with two other Norwegian cases, M.L. and Ibdi Ibrahim. It is proposed in line with the case-law of the ECHR the necessity of maintaining the right to visits of the biological parents during the situations of foster care, as well as the obligation by the domestic authorities and judicial courts to maintain the tight between parents and children making possible, when the circumstances allow it, the return of the child with his/her biological parents. Some recommendations for the practice of the Spanish authorities are established bearing in mind these case-law and it is exposed an example of good practice of permanent Foster care by the a Public institution, the Provincial Council of Guipuzcoa/Gipuzkoa.